HIV-1 RNA testing of pooled dried blood spots is feasible to diagnose acute HIV infection in resource limited settings. Issue 2 (3rd April 2018) - Dowling, Wentzel; Veldsman, Kirsten; Grace Katusiime, Mary; Maritz, Jean; Bock, Peter; Meehan, Sue-Ann; Van Schalkwyk, Marije; Cotton, Mark F; Preiser, Wolfgang; Van Zyl, Gert U
Abstract: Objectives: Rapid human immunodeficiency virus (HIV) antibody tests, routinely used for diagnosis in adults and older children in resource-limited settings (RLS), do not detect early HIV infections prior to seroconversion or when antibody levels are still low. Nucleic acid amplification to detect HIV-1 RNA is the most sensitive method for acute HIV infection diagnosis, but is costly. We therefore investigated HIV- 1 RNA testing of pooled dried blood spots (DBS) to diagnose acute HIV infection. Design: Laboratory-based investigation. Methods: DBS were collected from HIV-1 Voluntary Counselling and Testing (HVCT) clients who tested negative on the Advanced Quality TM HIV antibody rapid test. DBS samples from five participants were pooled and tested on the COBAS AmpliPrep/COBAS TaqMan HIV-1 (CAP/CTM) Test v2. Individual DBS were tested when pools tested positive (> 200 RNA copies/ml). Acute infection was confirmed by HIV viral load testing, two fourth-generation HIV serological assays, and Geenius™ HIV 1/2 Assay for antibody band identification. Results: Of 482 participants who were tested, one (0.2%) had acute HIV infection: Fourth generation serology was low-level positive, the plasma HIV viral load was 15 929 HIV-1 RNA copies/ml, gp160 and gp41 antibody bands were positive and the p31 band was negative, indicating a Fiebig Stage 5 infection. Conclusions: Pooled DBS HIV-1 RNA testing is efficient compared to individual testing for acute HIV infection diagnosis. Early identification of participants with acute HIV infection facilitates immediate initiation of antiretroviral therapy to improve immune recovery and prevent transmission to others.